Co-existence of chronic spontaneous urticaria with atopic dermatitis: clinical and immunological perspectives - Toubi, Elias; Mubariki, Raeda; Vadasz, Zahava (Frontiers in Allergy, 2025)
BackgroundChronic Spontaneous Urticaria (CSU) and Atopic Dermatitis (AD) are both immune-mediated inflammatory skin disorders that often co-exist with other atopic conditions such as asthma and allergic rhinitis. Their shared immunopathological pathways raise the question of a possible interrelationship.ObjectiveTo evaluate the prevalence, clinical features, and immunological profiles of AD in patients with CSU and to explore implications for diagnosis and treatment.Methods425 CSU patients treated in Northern Israel between 2021 and 2024, were retrospectively analyzed. Disease activity was assessed using the Urticaria Activity Score-7 (UAS7) and Investigators' Global Assessment (IGA) for AD. The prevalence of asthma, total serum IgE levels, and therapeutic responses were evaluated.ResultsAmong the 425 CSU patients, 42 (10%) were also diagnosed with AD. Co-morbid patients had a higher frequency of asthma (40%) and high total IgE levels (67%) compared to CSU-only patients. A substantial subset of co-morbid cases required biologic treatments with Dupilumab, offering benefit in AD-dominant cases unresponsive to Omalizumab. Severe CSU was more prevalent in the CSU + AD group (though the prevalence was not statistically significant).ConclusionCSU and AD frequently co-exist, likely due to overlapping T-cell–mediated immunopathogenic mechanisms. High total IgE and asthma comorbidity may indicate an underlying AD component in CSU patients. Recognition of this overlap is essential for appropriate therapeutic decision-making, including potential escalation to biologic agents targeting T-cell cytokine pathways.